"Amantyajana" Art Performance in the Implementation of the Independent Learning Curriculum at the Presiden's Senior High School - Fitriana Eka Putri; Dwi Kusumawardani; Indro Moerdisuroso (International Journal of Studies in International Education, 2025)
This study aims to describe the implementation of Merdeka Belajar Curriculum through Amantyajana art performance activities as project-based learning at Presidential High School. Using a qualitative descriptive approach, this study examines in depth the process of planning, implementing, and evaluating art activities developed collaboratively between teachers, students, and school parties. The results show that this art performance is not only a forum for students' artistic expression, but also a medium for character building, strengthening mutual cooperation values, and cross-subject integration in accordance with the Pancasila Student Profile. Amantyajana activities are designed thematically and contextually, involving students in all stages of production, from theme exploration, rehearsals, to public performances. Despite facing obstacles such as limited time, human resources, and infrastructure, this activity is still able to encourage meaningful, creative, and adaptive learning. Evaluation is conducted holistically through process assessment, performance, and student engagement in teamwork. The art performance proved to be a superior practice in actualizing the Merdeka Curriculum, which focuses on the meaningfulness of learning, active student participation, and cross-disciplinary collaboration.